Brain Derived Exosomes Are a Double-Edged Sword in Alzheimer’s Disease - Song, Zhiqi; Xu, Yanfeng; Deng, Wei; Zhang, Ling; Zhu, Hua; Yu, Pin; Qu, Yajin; Zhao, Wenjie; Han, Yunlin; Qin, Chuan (Frontiers in Molecular Neuroscience, 2020)
Brain derived exosomes (BDEs) are extracellular nanovesicles that are collectively released by all cell lineages of the central nervous system and contain cargo from their original cells. They are emerging as key mediators of communication and waste management among neurons, glial cells and connective tissue during both physiological and pathological conditions in the brain. We review the rapidly growing frontier of BDEs biology in recent years including the involvement of exosomes in neuronal development, maintenance and communication through their multiple signaling functions. Particularly, we highlight the important role of exosomes in Alzheimer’s disease (AD), both as a pathogenic agent and as a disease biomarker. Our understanding of such unique nanovesicles may offer not only answers about the (patho)physiological course in AD and associated neurodegenerative diseases but also ideal methods to develop these vesicles as vehicles for drug delivery or as tools to monitor brain diseases in a non-invasive manner because crossing the blood brain barrier is an inherent capability of exosomes. BDEs have potential as biomarkers and as therapeutic tools for AD and related brain disorders in the near future.